Case definitions for inclusion and analysis of endpoints in clinical trials for nonalcoholic steatohepatitis through the lens of regulatory science. Issue 5 (22nd February 2018) - Siddiqui, Mohammad Shadab; Harrison, Stephen A.; Abdelmalek, Manal F.; Anstee, Quentin M.; Bedossa, Pierre; Castera, Laurent; Dimick‐Santos, Lara; Friedman, Scott L.; Greene, Katherine; Kleiner, David E.; Megnien, Sophie; Neuschwander‐Tetri, Brent A.; et al.
Abstract : Nonalcoholic steatohepatitis (NASH) is an important cause of liver‐related morbidity and mortality. There are no approved therapies, and the results of clinical trials have been difficult to compare due to inconsistent definitions of relevant disease parameters in patients with NASH. The natural course of the disease has not been rigorously characterized, particularly with respect to the contributions of underlying obesity, type 2 diabetes, and other comorbidities and the treatments provided for these comorbidities. Efforts to perform analyses of pooled data are limited by heterogeneous case definitions used across studies to define disease states. There remains a major unmet need in the field to develop standardized definitions for populations for interventional trials. Such definitions are expected to impact how endpoints for clinical trials are constructed. The Liver Forum is a multistakeholder effort including US and European regulatory agencies, academic investigators, professional and patient representative organizations, and industry to catalyze therapeutic development for NASH by developing potential solutions to barriers to development. The Case Definitions Working Group was established by The Liver Forum to evaluate the validity of case definitions for populations to be included in clinical trials for NASH from a regulatory science perspective. Based on such analyses, specific recommendations are provided noting the strengths and weaknesses of the case definitions along with knowledge gaps that require additional study. (Hepatology 2018;67:2001‐2012)